Are two retrograde 3.5 mm screws superior to one 7.3 mm screw for anterior pelvic ring fixation in bones with low bone mineral density?. Issue 1 (January 2017) - Acklin, Y. P.; Zderic, I.; Grechenig, S.; Richards, R. G.; Schmitz, P.; Gueorguiev, B.
Abstract : Objectives: Osteosynthesis of anterior pubic ramus fractures using one large-diameter screw can be challenging in terms of both surgical procedure and fixation stability. Small-fragment screws have the advantage of following the pelvic cortex and being more flexible. The aim of the present study was to biomechanically compare retrograde intramedullary fixation of the superior pubic ramus using either one large- or two small-diameter screws. Materials and Methods: A total of 12 human cadaveric hemipelvises were analysed in a matched pair study design. Bone mineral density of the specimens was 68 mgHA/cm 3 (standard deviation (sd) 52). The anterior pelvic ring fracture was fixed with either one 7.3 mm cannulated screw (Group 1) or two 3.5 mm pelvic cortex screws (Group 2). Progressively increasing cyclic axial loading was applied through the acetabulum. Relative movements in terms of interfragmentary displacement and gap angle at the fracture site were evaluated by means of optical movement tracking. The Wilcoxon signed-rank test was applied to identify significant differences between the groups Results: Initial axial construct stiffness was not significantly different between the groups (p = 0.463). Interfragmentary displacement and gap angle at the fracture site were also not statistically significantly different between the groups throughout the evaluated cycles (p ⩾ 0.249). Similarly, cycles to failure were not statistically different between Group 1 (8438, sd 6968) and Group 2 (10 213, sd 10 334), p = 0.379. Failure mode in both groups was characterised by screw cutting through the cancellous bone. Conclusion: From a biomechanical point of view, pubic ramus stabilisation with either one large or two small fragment screw osteosynthesis is comparable in osteoporotic bone. However, the two-screw fixation technique is less demanding as the smaller screws deflect at the cortical margins. Cite this article: Y. P. Acklin, I. Zderic, S. Grechenig, R. G. Richards, P. Schmitz, B. Gueorguiev. Are two retrograde 3.5 mm screws superior to one 7.3 mm screw for anterior pelvic ring fixation in bones with low bone mineral density? Bone Joint Res 2017;6:8–13. DOI: 10.1302/2046-3758.61.BJR-2016-0261.